2022
DOI: 10.3390/ijerph19116732
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Structural Equation Modeling–Artificial Neural Network Hybrid Approach in Determining Factors Affecting Perceived Usability of Mobile Mental Health Application in the Philippines

Abstract: Mental health problems have emerged as one of the biggest problems in the world and one of the countries that has been seen to be highly impacted is the Philippines. Despite the increasing number of mentally ill Filipinos, it is one of the most neglected problems in the country. The purpose of this study was to determine the factors affecting the perceived usability of mobile mental health applications. A total of 251 respondents voluntarily participated in the online survey we conducted. A structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…This process implicated how the responses would be linked to members’ satisfaction with the national health insurance. Similar to the study of Yuduang et al [ 72 ], SEM and neural network analysis were conducted to verify the findings and close the limitations brought by SEM [ 49 ].…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…This process implicated how the responses would be linked to members’ satisfaction with the national health insurance. Similar to the study of Yuduang et al [ 72 ], SEM and neural network analysis were conducted to verify the findings and close the limitations brought by SEM [ 49 ].…”
Section: Methodsmentioning
confidence: 81%
“…The only response from the Likert Scale survey was considered in this study following the study of Ong et al [ 71 ]. In accordance, Yuduang et al [ 72 ] utilized a similar methodology following a data pre-processing stage. The collected data show that most females (52.8%) and males (46.8%) ranging from 18 to 75 years old are all collected around NCR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many mental health mobile applications that can help users relieve psychological stress, maintain mental health, and compensate for face-to-face counseling when necessary have also emerged. A recent study by Yuduang et al [ 7 ] found that people have little knowledge of the mental health services available online and that increasing awareness of online mental health services and understanding their benefits and accessibility would increase their willingness to use them. Therefore, studying the factors that influence people’s willingness to use online mental health services can help to better utilize online service platforms to promote mental health.…”
Section: Introductionmentioning
confidence: 99%